Role of the Anterior Center-Edge Angle on Acetabular Stress Distribution in Borderline Development Dysplastic of Hip Determined by Finite Element Analysis - Chen, Songhao; Zhang, Liqiang; Mei, Yuqian; Zhang, Hong; Hu, Yongcheng; Chen, Duanduan (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The joint with hip dysplasia is more likely to develop osteoarthritis because of the higher contact pressure, especially in the socket. The lateral center-edge angle (LCEA) is the major indicator for hip dysplasia via radiography. However, the pathological conditions of LCEA angles in the range of 18°–25° are still controversial, which challenges precise diagnosis and treatment decision-making. Objective: The purpose of this study is to investigate the influence of anterior center-edge angle (ACEA) on the mechanical stress distribution of the hip joint, via finite element analysis, to provide insights into the severity of the borderline development dysplasia. Methods: From 2017 to 2019, there were 116 patients with borderline developmental dysplasia of the hip (BDDH) enrolled in this research. Based on the inclusion criteria, nine patients were involved and categorized into three LCEA groups with the maximal ACEA differences. Patient-specific hip joint models were reconstructed from computed tomography scans, and the cartilages, including the labrum, were established via a modified numerical method. The finite element analysis was conducted to compare the stress distributions due to the different ACEA. Results: As ACEA decreased, the maximum stress of the acetabulum increased, and the high stress area developed toward the edge. Quantitative analysis showed that in the cases with lower ACEA, the area ratio of high stress increased, and the contact facies lunata area significantly affected the stress distribution. Conclusion: For patients with BDDH, both the ACEA and the area of facies lunata played essential roles in determining the severity of hip dysplasia and the mechanical mechanism preceding osteoarthritis.